Awareness regarding cardiac rehabilitation among patients with coronary heart disease attending a cardiac care centre, Kathmandu valley - Shrestha, Rosy; Shrestha, Sajeeb (Nepalese Heart Journal, 2019)
Introduction: Coronary heart disease (CHD) is gradually emerging as a leading cause of morbidity and mortality of many low middle income countries like Nepal. Cardiac rehabilitation awareness program has been proved to be effective for reducing the mortality as well as improving the quality of life among CHD patients. The aim of this study was to explore the awareness on cardiac rehabilitation (CR) in patients with CHD attending a cardiac care centre, Nepal. Method: A descriptive cross sectional study design was used to examine 100 CHD patients attending out-patient departments of Shahid Gangalal National Heart Centre (SGNHC), Kathmandu, Nepal. Purposive sampling technique was used for data collection by face to face interview technique with self developed tool. Data was analyzed with descriptive and inferential statistics. Results: Of all 100 respondents, 55.0% were male and the mean age was 53.23±14.22 years. The median score of awareness was 17 with interquartile range (IQR) 14.0-19.75 and majority (57.0%) of respondents were unaware about CR. The awareness regarding CR was found highest in awareness regarding CHD (75.0%) whereas lowest score was found in time and duration needed for exercise per week (14.0%). The significant influencing variables were age, education status, duration of treatment and participation in CR program for CHD patients. Conclusion: The awareness on CR program in CHD patients in Nepal is not optimal, especially among 54 and above age group, illiterate people, those receiving treatment equal & more than 1 year duration and the CHD patients who didn’t get chance to participate on awareness programs. Hence, it is strongly recommended that health professionals including nurses should organize and promote CR programs including counseling session to improve the awareness level and ultimately enhance quality of life of CHD patients.